2016
DOI: 10.1038/nchem.2644
|View full text |Cite
|
Sign up to set email alerts
|

Engineering genetic circuit interactions within and between synthetic minimal cells

Abstract: Genetic circuits and reaction cascades are of great importance for synthetic biology, biochemistry, and bioengineering. An open question is how to maximize the modularity of their design to enable the integration of different reaction networks and to optimize their scalability and flexibility. One option is encapsulation within liposomes which enables chemical reactions to proceed in well-isolated environments. Here we adapt liposome encapsulation to enable the modular, controlled compartmentalization of genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
351
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(355 citation statements)
references
References 52 publications
4
351
0
Order By: Relevance
“…Starting from the 'top-down' and removing as much complexity as possible yields 'minimal' cells [4]. The simplest living example to date is a stripped down version of Mycoplasma mycoides, JCV-syn3.0, with 473 genes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the 'top-down' and removing as much complexity as possible yields 'minimal' cells [4]. The simplest living example to date is a stripped down version of Mycoplasma mycoides, JCV-syn3.0, with 473 genes [5].…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] These studies utilized SNARE proteins and charge-charge interactions to initiate vesicle fusion, respectively,that provide an efficient method to drive vesicle fusion, but currently lack orthogonality that would allow for specific vesicle populations to be mixed simultaneously.T owards achieving this goal, we set out to determine the capacity of DNA-tethered vesicles to initiate protein synthesis in select populations of vesicles by inducing vesicle fusion. [5,6] These studies utilized SNARE proteins and charge-charge interactions to initiate vesicle fusion, respectively,that provide an efficient method to drive vesicle fusion, but currently lack orthogonality that would allow for specific vesicle populations to be mixed simultaneously.T owards achieving this goal, we set out to determine the capacity of DNA-tethered vesicles to initiate protein synthesis in select populations of vesicles by inducing vesicle fusion.…”
Section: Dna-mediated Vesicle Fusion Initiates Cell-free Synthesis Ofmentioning
confidence: 99%
“…While previous work has shown that lipid vesicles can be engineered to fuse in order to initiate cell-free reactions, [5][6][7] the ability to rapidly and noninvasively control fusion between specific populations of vesicles,w hile limiting off-target fusion to others,h as not yet been achieved. Targeted fusion could allow for such bioreactors to be reloaded with new reagents, promoting longer durations of product synthesis.M ultiple reactions could also be simultaneously executed in the same environment with limited opportunities for reaction crosstalk.…”
Section: Introductionmentioning
confidence: 99%
“…[2] For example,aprotocell model based on the spontaneous assembly of partially hydrophobic silica nanoparticles at the interface of water and oil to form water-in-oil Pickering emulsion droplets with amechanically robust membrane has been recently developed. Chemical communication and signalling have been demonstrated between populations of vesicles and bacteria, [12,13] lipid vesicles containing gene circuitry, [14] vesicles and proteinosomes, [15] colloidosomes, [16] modified [17] or immobilized [18] coacervate droplets,a nd in water-in-oil emulsion droplets. [11] Thee mergence of collective behaviour in mixed populations of synthetic protocells is relatively unexplored, even though increasing levels of protocell interactivity could provide more complex and synergistic functions,s uch as resilience to environmental stress,c hemical signalling for artificial quorum sensing,a nd multiplex tasking via collaboration and specialization.…”
mentioning
confidence: 99%
“…Thei norganic membrane was crosslinked to produce shell-like micro-compartments (colloidosomes) that could be transferred to water and endowed with biomimetic functions,s uch as in situ gene expression, [6] enzyme-mediated catalysis, [6,7] microcapsule growth and divi-sion, [8] membrane gating, [9] enzyme-directed secretion of an extracellular-like matrix, [10] and energy capture and conversion. Chemical communication and signalling have been demonstrated between populations of vesicles and bacteria, [12,13] lipid vesicles containing gene circuitry, [14] vesicles and proteinosomes, [15] colloidosomes, [16] modified [17] or immobilized [18] coacervate droplets,a nd in water-in-oil emulsion droplets. Chemical communication and signalling have been demonstrated between populations of vesicles and bacteria, [12,13] lipid vesicles containing gene circuitry, [14] vesicles and proteinosomes, [15] colloidosomes, [16] modified [17] or immobilized [18] coacervate droplets,a nd in water-in-oil emulsion droplets.…”
mentioning
confidence: 99%